2022
DOI: 10.1155/2022/1624446
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of miR-221-3p by LncRNA TUG1 Promoting the Healing of Closed Tibial Fractures in Mice

Abstract: Objective. To probe into the effect of LncRNA TUG1 on the healing of closed tibial fracture in mice. Methods. The closed tibial fracture model of mice was established, selecting the mouse osteoblast line MC3T3-E1, with the cells separated into four groups. The expression levels of TUG1 and miR-221-3p were determined by RT-qPCR analysis, with the targeting relationship between TUG1 and miR-221-3p authenticated by dual luciferase reporter (DLR) assay, detection of cell migration (CM) ability based on Transwell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%